Pengembangan Anyaman Mansiang dengan Inovasi Produk dan Pemasaran dengan Media Sosial di Taratak Kenagaraian Kubang, Kecamatan Guguak Kabupaten Lima Puluh Kota - Ratni Prima Lita; Verinita Verinita; Ranny Fitriana Faisal; Bintang Rizky Abdullah Majo Saibah; Werianton Weriantoni; Syuryatman Desri; Winny Alna Marlina; Erizal Nazaruddin; Devi Yulia Rahmi; Fatma Poni Mardiyah; Nur Ari Sufiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Taratak village is one of the Jorongs in Nagari Kubang, Guguak District, Lima Puluh Kota Regency, and West Sumatra. Taratak is a natural village with a creative business, namely Mansiang leaf craft. There are seven groups of Mansiang leaf craftsmen in Taratak. The social activity was carried out in 3 stages, namely the preparation stage, starting with obtaining permits, socializing with related institutions, and contacting artisans to decide on the schedule for activities. Activities were carried out using training, practice and mentoring methods. At the monitoring and evaluation stage, activities were carried out to evaluate and monitor the implementation of activities. The results of the activity include product innovation with embroidery, increasing product variants, and creating social media for marketing, i.e. Facebook, Twitter and Instagram.